Enhancing Literacy and Numeracy in Indonesian Elementary Schools: Principal Led Strategies in a Resource-Limited - Amri, Amri; Murniati, Murniati; Usman, Nasir; Fajri, Munawar (Edukasi, 2026)
This study examines how school principals plan, implement, and evaluate literacy- and numeracy-oriented learning programs in Cluster 1 elementary schools in Krueng Sabee, as well as the challenges they face in improving students’ learning outcomes in resource-limited contexts. Employing a qualitative case study design, data were collected over a three-month period from six school principals, teachers, and seven school committee members through semi-structured interviews, classroom observations, and document analysis. Data analysis followed Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing, while trustworthiness was ensured through source and method triangulation and member checking. The findings reveal three principal-led strategies: (1) strategic distribution of reading and numeracy resources to support integrated literacy–numeracy learning; (2) principal leadership in enhancing teacher competence through literacy and numeracy interventions; and (3) school-wide initiatives and collaborative team support that strengthen students’ motivation toward literacy. Despite limitations in facilities and learning resources, principals demonstrated adaptive and collaborative leadership that enabled schools to optimize available resources and sustain literacy and numeracy programs. Overall, the study confirms that focused and systematic principal leadership plays a critical role in strengthening literacy and numeracy learning in elementary schools operating under resource constraints.